Employment and Wage Effects of Trade Liberalization: The Case of Mexican Manufacturing - Revenga, Ana (Journal of Labor Economics, 1997)
This article analyzes the effect of trade liberalization on employment and wages in the Mexican manufacturing sector. The study documents that many of the rents generated by trade protection were absorbed by workers in the form of a wage premium. Trade liberalization affected firm‐level employment and wages by shifting down industry product and labor demand. This in itself may have accounted for a 3%–4% decline in real wages on average. But trade reform also reduced the rents available to be captured by firms and workers. This had an additional negative effect on firm‐level employment and wages.